Influence of clinical and neurocognitive factors in psychosocial functioning after a first episode non-affective psychosis: differences between males and females - Serra-Navarro, Maria; Amoretti, Silvia; Verdolini, Norma; Forte, María Florencia; Sánchez-Torres, Ana M.; Vieta, Eduard; Clougher, Derek; Lobo, Antonio; González-Pinto, Ana; Panadero, Rocío; Roldán, Alexandra; Carvalho, André F.; et al. (Frontiers in Psychiatry, 2022)
Background: Deficits in psychosocial functioning are present in the early stages of psychosis. Several factors, such as premorbid adjustment, negative symptoms, neurocognitive performance, and cognitive reserve (CR), potentially influence functionality. Sex differences are observed in patients with psychosis in multiple domains. Nonetheless, few studies have explored the predictive factors of poor functioning according to sex in first-episode psychosis (FEP). This study aimed to explore sex differences and identify predictors of functioning according to sex after onset. Methods: The initial sample comprised 588 individuals. However, only adult patients with non-affective FEP (n=247, 161 males and 86 females) and healthy controls (n=224, 142 males and 82 females) were included. A comprehensive assessment including functional, neuropsychological, and clinical scales were performed at baseline and at 2-year follow-up. A linear regression model was used to determine the predictors of psychosocial functioning at 2-year follow-up. Results: The variables associated with worse functioning at follow-up were: for males (F=8.676, p<0.001), higher severity of negative symptoms (β=0.246, p=0.044), worse premorbid adjustment (β=0.247, p=0.050) and worse sustained attention (β=0.276, p=0.027); for females (F=8.433, p<0.001), worse processing speed (β= 0.410, p=0.005) and lower CR (β= 0.471, p=0.002). Conclusions: Our data indicate that predictors of functioning at 2-year follow-up in FEP patients differ according to sex. Therefore, treatment and preventative efforts may be adjusted taking sex into account. Males may benefit from an intervention focused on negative symptoms and cognitive remediation, even at early stages. Conversely, in females, the implementation of early interventions centered on CR enhancement may be recommended.